Movement Skills Learning Model in Physical Education Against Psychological Student Personality: A Systematic Riview - Alfani, Muhammad Aliffajaruddin; sugiharto, Sugiharto (Universitas Suryakancana, 2022)
The right motion learning model in physical education will improve the psychological aspects of the student's personality. however, different subjects and interventions should have different impacts. The purpose of this study is to review learning models in physical education that relate to the psychological aspects of students from elementary to high school. The method used is a systematic review, using secondary data from published journals. Data collection was carried out manually outside the database and with the help of access to the Google Scholar database. In searching the data, keywords that are relevant to the topic to be discussed are used. The keywords used were â€œpsychological personalityâ€ AND â€œemotionalâ€ AND â€œmentalâ€ AND â€œsocial behaviorâ€ AND â€œphysical educationâ€. After that, an analysis will be carried out using a prisma flowchart diagram. The results of filtering data according to the inclusion and exclusion criteria are 20 national and indexed Sinta journals. Based on the results of the analysis of various models, the application of the outdoor physical education learning model and the cooperative model is more widely applied to junior high school students and above. Meanwhile, elementary schools apply more game-based learning. Therefore it is important for educators to know and understand the characteristics of each student for the selection of learning models so that it has a positive impact on aspects of the psychological personality of students.Key words: Learning Model, Physical Education,Â Personality Psychology.